Simulações computacionais de eletrólitos em interfaces - Cardoso, Pierluigi Fortunato [UNIFESP] (2018)
In this work the molecular dynamics, which is a computational simulation method, is used for the study of electrical, structural and dynamics properties of electrolytes for lithium and / or supercapacitor batteries. The electrolytes formed by ionic liquid and polymer were simulated at the interface with a flat electrode model, ionic liquid (IL), P(EO)7,8-IL, P(EO)15,6-IL e P(EO)15,6-Li+-IL at different densities of charges, 0q/nm2, 0,25 q/nm2, 0,5q/nm2, 0,75 q/nm2 and 1,0 q/nm2. The potential drop were calculated and assisted the analysis of the differential capacitances, being possible to observe the effect of the polymer poly (ethylene oxide) that acted like solvent, causing the decrease of the overscreening in relation to the system composed only by ionic liquid [EMIm]-[TFSI]. In this way, it was possible to calculate the differential capacitances that were also calculated for the different systems, noting that the increase in the number of molecules of PEO influences the decrease of the differential capacitances for each of the systems, such as the P(EO)15,6-IL, which has the highest amount of polymer PEO, had the lowest differential capacitance (3.4 on the positive electrode and 2.9 on the negative electrode) in relation to the other systems studied. In the case of batteries, the values obtained for the lithium ion to adsorb on the surface of the negative electrode is between 3,66V ~ 5,74V.